Making Memories: Time and Responsibility in Intermedial Metatheatre - Gasoi, Lowell (Intermédialités / Intermediality, 2019)
That performance can be captured and replayed may be a given, but much less well-understood is the relationship between that stored performance, the memory of a performed act, and the live event. The practice of intermedial theatre offers a unique way to probe that relationship, and the awareness of metatheatre further exposes the links between memory, technology, and performance. This paper argues that intermedial metatheatre, and my own work as a director, video-maker, and video performer for a 2014 production of Daniel MacIvor’s play Never Swim Alone, provides a valuable model for research-creation that can shed light on these questions in an embodied and experiential manner. Engaging with Sarah Kember and Joanna Zylisnka’s notion of performative media, as well as the concept of memory work from Annette Kuhn, I offer thoughts on materiality, time, and mediated memory, captured through technologies like camera and sound recording equipment, and in constructed spaces like studios and rehearsal rooms, represented by projection mapping software and digital projectors in the theatre space. All these are integrated into the network of actors and techniques that make up current practices in intermedial theatrical creation. Can this research begin to unravel ideas of authenticity and liveness when reactivating memories in relation to live actors, and before an audience? And what of our responsibility to the digital representation and the live performer when bringing these memories and moments together? How does the network of technologies and practitioners in intermedial theatre creation and presentation, understand and respect the “lifeness” of a mediated memory?